Foliar chlorophyll concentration modulates the degree of fungal exploitation in a rhizoctonia-associated orchid. (21st March 2022) - Suetsugu, Kenji; Matsubayashi, Jun
Abstract : This study strongly suggests that a rhizoctonia-associated orchid can dynamically adjust fungal exploitation to overcome the shortage of photosynthetic carbon. Trophic plasticity in green orchids may be a widespread adaptive trait. Abstract: Some green orchids obtain carbon from both mycobionts and photosynthesis at the adult stage. Intriguingly, these orchids can produce albino and, in rare cases, variegated phenotypes. Here, we studied a Platanthera hondoensis population with green, variegated, and albino individuals. Although its closely related Platanthera species are usually associated with non-ectomycorrhizal rhizoctonias, and several studies have failed to find evidence of trophic plasticity in rhizoctonia-associated orchids, variegated and albino P. hondoensis must possess a higher fungal dependency than green P. hondoensis . Therefore, we investigated whether (i) P. hondoensis is associated with non-ectomycorrhizal rhizoctonias and (ii) the degree of mycoheterotrophy (using 13 C abundance as a proxy) correlates with the foliar chlorophyll concentration. High-throughput DNA sequencing revealed that all P. hondoensis phenotypes were dominantly associated with a rhizoctonia from Ceratobasidiaceae belonging to a clade distinct from recognized ectomycorrhizal clades. Regression analysis revealed a positive linear relationship between foliar chlorophyll concentration and the degree of mycoheterotrophy. This study strongly suggests that rhizoctonia-associated P. hondoensis can dynamically adjust fungal exploitation in response to photosynthetic carbon levels. Since rhizoctonia is the most common orchid mycorrhizal partner, trophic plasticity may be a widespread adaptive trait in green orchids.